An enhanced harmony search algorithm for assembly sequence planning. (1st January 2013) - Wang, Lijian; Hou, Yuxing; Li, Xinyu; Sun, Shuai
Assembly sequence planning (ASP) plays a critical role in manufacturing and product design. A good assembly sequence can help reduce the cost and time of manufacturing process. However, ASP is difficult to be tackled; the size of the search space of assembly sequences is exponentially proportional to the number of components of assembly products. Compared with traditional graph-based algorithm, the intelligent optimisation algorithms have exhibited their advantages in finding optimal assembly sequence. In this paper, harmony search (HS) is proposed to help solve the ASP problem. HS algorithm has been successfully applied to continuous-variable as well as combinatorial optimisation problems. To further strengthen the optimisation performance and be more effectively used for ASP problem, the proposed method incorporates the largest position value (LPV) rule and an efficient switching strategy of local search. The developed approach is validated with an illustrative example and the results are compared with those obtained using traditional genetic algorithm (GA) and memetic algorithm (MA). The result shows the proposed approach has achieved significant improvement.